Microelectrode-Based Electrochemical Sensing Technology for in Vivo Detection of Dopamine: Recent Developments and Future Prospects. (11th April 2022) - He, Cailing; Tao, Mengdan; Zhang, Chenxi; He, Yifang; Xu, Wei; Liu, Yan; Zhu, Wanying
Abstract: Dopamine (DA) is an essential type of neurotransmitter in the central nervous system. DA neurons usually exist as nuclei which are mainly found in the ventral tegmental area (VTN) and substantia nigra pars compacta (SNc). Parkinson's disease, epilepsy, schizophrenia and other diseases are all related to the abnormal metabolism of DA. Compared with traditional DA detection methods such as spectrophotometry and electrophoresis, electrochemical sensing technology has high detection efficiency, high sensitivity, fast and convenient real-time detection, which is recognized as the most effective method for measuring neurotransmitters in vivo. The working electrode of an electrochemical sensor can be generally divided into the conventional electrode and the microelectrode according to its size. The microelectrode shows excellent properties such as high sensitivity, high temporal resolution, and high spatial resolution while detecting DA, which makes it possible to detect neurotransmitters in vivo. In order to further investigate the role of DA in regulating action, emotion, and cognition, and to further clarify the relationship between DA abnormalities or lack and neurological diseases such as Parkinson, more and more researchers apply microelectrode-based electrochemistry sensing technology to detect DA in vivo. This article reviews recent applications of microelectrodes and the latest researches in DA detection in vivo, focusing on the following three types of microelectrodes: (1) non-nanomaterial-modified carbon fiber microelectrodes (CFE); (2) nanomaterial-modified microelectrodes; (3) microelectrode arrays (MEA).